THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND THE GROWTH AND DEVELOPMENT OF INFANTS AGED 6–12 MONTHS IN THE WORKING AREA OF UPTD PUSKESMAS KARANG INTAN 1 IN 2025 - Henny Nurhayati; Vonny Khresna Dewi; Hapisah Hapisah (Health Sciences Journal, 2026)
Exclusive breastfeeding is recognized as the optimal source of nutrition for infants and plays a crucial role in supporting growth and developmental outcomes during early life. Based on 2024 profile data, it was recorded as the area with the fifth-lowest exclusive breestfeeding rate, with only 18 (17,3%) of 104 babies receiving exclusive breastfeeding. To determine the relationship between exclusive breastfeeding and the growth and development of infants aged 6–12 months in the working area of Puskesmas Karang Intan 1.. This study used a quantitative design with a cross-sectional approarch. The population in this study was 61 mothers with infants aged 6-12 moths usiang a purposive sampling technique. The dependent variable in this studi was infant growth and development, while the independent variable was this history of exclusive breastfeeding. Analysis used the Chi-Square test with a significance value of 0,05. 31 (81,6%) infants received exclusive breastfeeding. 35 (92,1%) infants had normal growth. 32 (84,2%) infanst developed according to their age. Statistical test showed a relationship between a history of exclusive breastfeeding and the growth and development of infants aged 6-12 months with a p-value of 0,000 (p<0,05). There is a relationship between the history of exclusive breastfeeding and growth and development in infants aged 6-12 months in the working area a Karang Intan 1 Health Center in 2025. Keywords: exclusive breastfeeding, growth, development, infants, KPS